ANALISIS VALUE ADDED SEBAGAI INDIKATOR INTELLECTUAL CAPITAL DAN KONSEKUENSINYA TERHADAP KINERJA PERBANKAN - Eko Wibowo; Arifin Sabeni (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to analyse the role of value added (VA) especially the value added of intellectual capital coefficient (VAIN) and value added capital employed coefficient (VACA) as an indicator of intellectual capital (IC). By using The Pulic Model (Value Added Intellectual Coefficient – VAIC™) as the measure of IC and that consequency to the ﬁrm’s economic (OIS), ﬁnancial (ROA)and stock market performance(MB)on banking companies. Data from this study were obtained from financial statements and annual reports of  banking companies drawn from the Indonesia Stock Exchange. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange during the years 2009-2011 for 25 companies. Determination of the sample using purposive sampling method. The type of data used are secondary data in the form of annual reports by the media banking companies. Data analysis tools that use the Multivariate Analize with the help of a computer program SPSS. The results of this study indicate there is a possitive association between the value added of intellectual capital (VAIN) and financial performance (ROA) and the ﬁrm’s economic (OIS), but have no association on stock market performance(MB) on Indonesia banking companies. The results also show that the valueadded capital employed (VACA)  has a positive association on the ﬁrm’s economic (OIS) and stock market performance (MB), but the value added capital employed (VACA) have no association on ﬁnancial performance (ROA) on Indonesia banking companies.